Equity in FEMA hazard mitigation assistance programs: The role of state hazard mitigation officers. Issue 136 (October 2022) - Vilá, Olivia; Smith, Gavin; Cutts, Bethany; Gyawali, Samata; Bhattarai, Samiksha
Abstract: FEMA provides hundreds of millions of dollars for hazard mitigation projects annually through their Hazard Mitigation Assistance (HMA) grant programs. HMA funding is most accessible to resource-rich communities leaving historically underserved communities that are often more vulnerable to disasters less able to obtain federal mitigation funding. This research highlights the results of a national survey conducted with 43 State Hazard Mitigation Officers (SHMOs), assigned state-level leaders who can have great influence on mitigation equity within their state. The survey explored the role of states and territories in facilitating mitigation equity in FEMA HMA programs using a three-pillar environmental justice framework (recognition, procedural justice, and distributional justice). The results indicate state-level shortcomings, including limited understanding of underserved communities, poor procedures for identifying and engaging with underserved communities, and limited local engagement in state- or territory-sponsored conferences, trainings, meetings, and policy discussions. The results yield insight into some of the underlying processes through which inequities in federal support for mitigation emerge and provide guidance to address shortcomings. These findings have important implications for federal- and state-level policy aiming to promote equity in hazard mitigation. Specifically, they point to the need for assessments of the needs, values, and priorities of low-capacity communities, identification and outreach strategies tailored to those communities, and increased financial and technical assistance for equity-focused actions. This study underscores the value of environmental justice research in decision-making associated with multi- billion- dollar federal grant programs. Highlights: SHMO's recognition of low-capacity communities is relatively limited. Engagement processes are not tailored to the qualities of those communities. Assistance for recognition-based activities is necessary for equitable outcomes.